Case report: Transcatheter tricuspid valve intervention using K-Clip™ system after prior Kay’s annuloplasty - Wu, Shengjun; Dai, Xiaoyi; Liu, Lingshan; Yuan, Shuai; Teng, Peng; Ni, Yiming (Frontiers in Cardiovascular Medicine, 2023)
The K-Clip™ system is emerging as an alternative to correct tricuspid regurgitation (TR) for patients with high surgical risk. However, patients with recurrent severe tricuspid regurgitation after prior Kay’s annuloplasty are not generally deemed to be candidates for K-Clip™ implantation. Herein, we report a case of a 63-year-old woman with recurrent symptomatic torrential tricuspid regurgitation 5 years after double valve replacement with Kay’s annuloplasty of the tricuspid valve. The K-Clip™ was successfully implanted, and the severity of tricuspid regurgitation and dimensions of tricuspid annulus achieved significant reduction. In conclusion, K-Clip™ can still be feasible and effective for patients with prior Kay’s annuloplasty. However, indications become more rigorous, and evaluation should be more comprehensive.